Loss-of-function Alleles of Heading date 1 (Hd1) are Associated with Adaptation of Temperate Japonica Rice Plants to the Tropical Region - Kim, Sung-Ryul; Torollo, Gideon; Yoon, Mi-Ra; Kwak, Jieun; Lee, Choon-Ki; Prahalada, G.D.; Choi, Il-Ryong; Yeo, Un-Sang; Jeong, O-Young; Jena, Kshirod K.; Lee, Jeom-Sig (Frontiers Media, 2018)
Adaptation of temperate japonica rice varieties to tropical regions is impeded by extremely early flowering probably due to photoperiod change from long to short. However, constant breeding efforts led to development of temperate japonica varieties adapted to tropical/subtropical regions, but the genetic factor underlying this is still elusive. We analyzed the 45 diverse rice accessions and 12 tropical-adapted temperate japonica lines for the allele types of seven major flowering genes Hd1, OsPPR37, DTH8, Ghd7, Ehd1, RFT1, and Hd3a and flowering time under three different field conditions in temperate and tropical locations. The accessions originated from the tropical/subtropical regions preferred the nonfunctional alleles of Hd1 and not other flowering genes. The genetic effect analysis of each gene showed that only the functional Hd1 caused early flowering in the tropical location. All 12 temperate japonica breeding lines adapted to the tropics possessed the loss-of-function alleles of Hd1 with no change of other flowering genes compared to common Korean temperate japonica varieties. A phylogenetic analysis using 2,918 SNP data points revealed that the genome status of the 12 breeding lines were very similar to Korean temperate japonica varieties. These results indicate that the functional Hd1 alleles of temperate japonica varieties induced extremely early flowering in the tropics and the nonfunctional hd1 alleles brought about the adaptation of temperate japonica rice to tropical regions